DIGITAL COMPETENCY AND HUMAN RESOURCE MANAGEMENT STRATEGIES IN THE DIGITAL ERA: CHALLENGES FOR CAREER READINESS OF GENERATION Z - Diar Widyardi (Universitas La Tansa Mashiro, 2026)
This study investigates how digital competency and the human resources management (HRM) strategies plays a role in increasing generation Z career readiness in facing the digital era. Because of the fast growth of digital technology, workforce needs have changed, asking workers to have responsive skills and strong digital literacy. This research employed a qualitative approach with a case study design involving Generation Z graduates in Indonesia. Data were collected through in-depth interviews and documentation, and analyzed using thematic analysis. The findings indicate that digital competency, including the ability to use digital tools, online communication platforms, and self-directed learning resources, plays a significant role in enhancing career readiness. In addition, HRM strategies such as training, mentoring, and digital-based performance evaluation effectively support skill development and employability. However, several challenges remain, including skill gaps, lack of practical experience, and limited access to high-quality training. This study concludes that integrating digital competency development with adaptive HRM strategies is essential to prepare Generation Z for the dynamic labor market in the digital era.